In-hospital mortality associated with community-acquired pneumonia due to methicillin-resistant Staphylococcus aureus: a matched-pair cohort study - Yukiyo Sakamoto (BMC, 2021)
Abstract Background It remains unclear whether methicillin-resistant Staphylococcus aureus (MRSA) pneumonia is associated with higher mortality compared with non-MRSA pneumonia. This study’s objective was to compare outcomes including in-hospital mortality and healthcare costs during hospitalisation between patients with MRSA pneumonia and those with non-MRSA pneumonia. Methods Using a national inpatient database in Japan, we conducted a 1:4 matched-pair cohort study of inpatients with community-acquired pneumonia from 1 April 2012 to 31 March 2014. In-hospital outcomes (mortality, length of stay and healthcare costs during hospitalisation) were compared between patients with and without MRSA infection. We performed multiple imputation using chained equations followed by multivariable regression analyses fitted with generalised estimating equations to account for clustering within matched pairs. All-cause in-hospital mortality and healthcare costs during hospitalisation were compared for pneumonia patients with and without MRSA infection. Results Of 450,317 inpatients with community-acquired pneumonia, 3102 patients with MRSA pneumonia were matched with 12,320 patients with non-MRSA pneumonia. The MRSA pneumonia patients had higher mortality, longer hospital stays and higher costs. Multivariable logistic regression analysis revealed that MRSA pneumonia was significantly associated with higher in-hospital mortality compared with non-MRSA pneumonia (adjusted odds ratio = 1.94; 95% confidence interval: 1.72–2.18; p < 0.001). Healthcare costs during hospitalisation were significantly higher for patients with MRSA pneumonia than for those with non-MRSA pneumonia (difference = USD 8502; 95% confidence interval: USD 7959–9045; p < 0.001). Conclusions MRSA infection was associated with higher in-hospital mortality and higher healthcare costs during hospitalisation, suggesting that preventing MRSA pneumonia is essential.